2006
DOI: 10.1210/en.2005-1281
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Glutathione Depletion and Follicle-Stimulating Hormone on Reactive Oxygen Species and Apoptosis in Cultured Preovulatory Rat Follicles

Abstract: Oxidative stress and depletion of the antioxidant glutathione (GSH) trigger apoptosis in many systems. Previous work showed that antioxidants prevented apoptosis as effectively as FSH in preovulatory follicles. We aimed to test the hypotheses that follicular reactive oxygen species (ROS) initiate apoptosis and that follicular GSH protects against apoptosis. Preovulatory follicles were isolated from ovaries of immature rats primed with pregnant mare serum gonadotropin. Negative control (0-h) follicles were proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 74 publications
9
104
0
1
Order By: Relevance
“…In this research, the levels of these enzymes were significantly (P<0.05) inhibited by DON compared with the control, indicating that DON could induce oxidative stress in laying hens. This result is consistent with the previous research described above, and studies have also found that oxidative stress affects the female reproductive system by inhibiting follicle cell growth [26,27] or by even damaging ovarian and uterine cells. This is the probable explanation for why the DON group exhibited a lower egg production rate (71.15%) compared with the other groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this research, the levels of these enzymes were significantly (P<0.05) inhibited by DON compared with the control, indicating that DON could induce oxidative stress in laying hens. This result is consistent with the previous research described above, and studies have also found that oxidative stress affects the female reproductive system by inhibiting follicle cell growth [26,27] or by even damaging ovarian and uterine cells. This is the probable explanation for why the DON group exhibited a lower egg production rate (71.15%) compared with the other groups.…”
Section: Discussionsupporting
confidence: 93%
“…The selenium nanoparticle (SeNP), which is one form of elemental selenium (Se0), has lower toxicity and better absorption and it is most effective when provided to broiler chicken under oxidative stress with the same dose but different sources of Se (organic, inorganic and nano-Se) [28]. According to some studies, the size of SeNPs synthesized by microorganisms has mostly been between 20 and 300 nm [20,26,27], and the diameter of the SeNPs in this research was 50 to 110 nm, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular GSH depletion is capable of sensitizing many types of cells to apoptosis; 19,20 however, little is known concerning the relationship between intracellular GSH loss and Na þ ,K þ -ATPase. In present study, Fas L decreased the intracellular GSH content as early as 30 min (data not shown), consistent with Fas L-induced inhibition of Na þ ,K þ -ATPase transport activity (Figure 1c).…”
Section: Intracellular Gsh Depletion Triggers the Internalization Andmentioning
confidence: 99%
“…The present results indicate that massive ovulation may aggravate oxidative stress in laying hens. In vitro studies have shown that excessive ROS generation inhibits follicular development, induces granular cell apoptosis, and causes follicular atresia (26)(27)(28)(29)(30). The decline of ovarian function in modern laying hens may be associated with oxidative stress induced by massive ovulation.…”
Section: Discussionmentioning
confidence: 99%